Microwave‐assisted Synthesis of Pd Oxide‐rich Pd Particles on Nitrogen/Sulfur Co‐Doped Graphene with Remarkably Enhanced Ethanol Electrooxidation. Issue 1 (19th December 2016) - Zhang, J. X.; Yang, X. L.; Shao, H. F.; Tseng, C. C.; Wang, D. S.; Tian, S. S.; Hu, W. J.; Jing, C.; Tian, J. N.; Zhao, Y. C.
Abstract: Nitrogen and sulfur co‐doped graphene supported Pd oxide‐rich (PdOx ‐rich) Pd nanoparticles (Pd/NS‐rGO) are synthesized by microwave‐assisted ascorbic acid reduction method. Raman spectrum reveals that the introduced NS co‐doping could introduce more defects on the graphene surface. X‐ray diffraction, X‐ray photoelectron spectrum, SEM and TEM images indicate that the synthesized PdOx ‐rich Pd particles are well‐dispersed on NS co‐doped graphene surface. Cyclic voltammograms curves illustrate that the Pd/NS‐rGO catalyst exhibits a larger electrochemically active surface area (35.7 m 2 g −1 ) and higher positive current density (1, 054.0 mA mg −1 Pd) than other catalysts prepared by similar methods. The Pd/NS‐rGO catalyst also reveals superior anti‐poisoning intermediate species ability and amazing stability. The electrocatalytic mechanism is also detailedly discussed and the designed Pd/NS‐rGO catalyst has opened up a new insight and methodology for the construction of a high performance and stability ethanol electrocatalysts in corrosive alkaline environments.